Relationship Between Daily Meteorological Parameters and Stab Wounds, Firearm Wounds and Assault - Yilmaz, Mustafa; Goktekin, Mehmet Cagri; Bork, Turgay (My University, 2024)
Introduction: In this study, we aimed to investigate the effect of daily meteorological parameters on the number of patients applying to the emergency department as a result of exposure to aggressive behavior. Methods: In our retrospectively planned study, patients who were admitted to the university hospital emergency department between January 1, 2012, and December 31, 2021, due to stab wounds, gunshot wounds, and assault were included in the study. The relationship between the meteorological parameters, including air temperature, atmospheric pressure, relative humidity, and maximum wind speed on the admission days of these patients, was analyzed. Results: In the study, a total of 7825 patients admitted due to stab wounds (n=1110), gunshot wounds (n=681), and assault (n=6034) were included. The highest number of applications to the emergency department due to exposure to physical violence were on Fridays (n=1225, 16%) and in August (n=780, 10%), and the lowest applications were on Sundays (n=1014, 13%) and in February (n=428, 6%). According to the results of the Poisson regression analysis of the relationship between patient applications and daily measurement parameters, average relative humidity and average wind speed were found to be independent determinants for stab wounds and gunshot wounds, and average temperature and average wind speed were found to be independent determinants for assault. Discussion and Conclusion: Meteorological parameters such as air temperature, relative humidity, air pressure, and maximum wind speed affect exposure to aggressive behavior and the need for emergency healthcare.
Keywords: Pressure; Temperature; Air; Humidity; Wind Speed; Assault; Firearm Wounds; Stab Wounds